2016
DOI: 10.1097/mpa.0000000000000588
|View full text |Cite
|
Sign up to set email alerts
|

Recent Trends in Survival of Patients With Pancreatic Cancer in Germany and the United States

Abstract: Although pancreatic cancer survival continues to be poor for advanced-stage patients, our study disclosed encouraging indications of first improvements in 5-year RS after decades of stagnation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
60
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(66 citation statements)
references
References 35 publications
3
60
0
3
Order By: Relevance
“…The median age of patients suffering from pancreas cancer is 70 years or more[2]. Even though pancreatectomies have been proven safe for patients older than 70 years[3], significant disparities have been noted in the elderly receiving appropriate surgical treatment for pancreatic cancer[4].…”
Section: Introductionmentioning
confidence: 99%
“…The median age of patients suffering from pancreas cancer is 70 years or more[2]. Even though pancreatectomies have been proven safe for patients older than 70 years[3], significant disparities have been noted in the elderly receiving appropriate surgical treatment for pancreatic cancer[4].…”
Section: Introductionmentioning
confidence: 99%
“…Table IV shows the 5-year observed and relative survival by age group (15-34, 35-44, 45-54, 55-64, 65-74, and 75+) for all the major cancer sites. Relatively higher survival rates were observed in younger patients (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44) compared with older patients (65-74, 75+), particularly for sites including the stomach, lung, pancreas, B and CNS, blood (NHL) and cervix. Cancer of the oesophagus, female breast and bladder had higher survival in middle-aged groups (45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)…”
Section: Resultsmentioning
confidence: 99%
“…However, clinicians should be mindful that surgery is the only curative option for pancreatic carcinomas (PCs), and elderly patients are often less likely to tolerate chemotherapy owing to significant age-related comorbidities. The 5-year survival rate of PCs in Germany is 10.7% and only 20% of 51 diagnosed patients are even suitable for pancreatic resection [1] . However, our study found that surgery significantly increased the 5-year survival rate of the elderly cohort to 14.1%, and there was even a trend toward higher R0 resection rates.…”
Section: Discussionmentioning
confidence: 99%
“…With reference to this demographic trend, the older patient population will inevitably be confronted with the need for surgical intervention in the future. In pancreatic surgery, it is especially important to consider these demographic changes, because there is a strong correlation between the incidence of malignant tumors and advanced age [1] .…”
Section: Introductionmentioning
confidence: 99%